Pemanfaatan Limbah Upacara (Canang) Menjadi Bahan Baku Briket Sebagai Sumber Energi Alternatif Ramah Lingkungan - Andika, Ida Bagus Made Baskara; Swari, I Gusti Agung Ratih Pradnya; Saguna, I Gusti Ngurah Agung Indra; Ananda, I Gusti Ngurah Agung Satria (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2026)
Canang waste, a type of organic waste from Balinese Hindu offerings, is commonly produced in traditional villages such as Desa Tihingan. This study aims to utilize canang waste as raw material for briquette production. The method employed is experimental, involving stages such as material collection, drying, shredding, carbonization, sieving, mixing, molding, and drying. Samples were tested using a bomb calorimeter to determine their Higher Heating Value (HHV) and Lower Heating Value (LHV). The results showed that canang briquettes have an HHV of 21.27 MJ/kg and an LHV of 19.64 MJ/kg, which are higher than those of mixed organic briquettes (HHV: 20.62 MJ/kg, LHV: 18.47 MJ/kg), but lower than prapen charcoal (HHV: 26.95 MJ/kg, LHV: 25.82 MJ/kg). These findings indicate that canang briquettes have potential as a viable alternative fuel. Moreover, this approach offers an environmentally friendly and sustainable solution for managing ceremonial waste.